Disorders of sex development: insights from targeted gene sequencing of a large international patient cohort. Issue 1 (December 2016) - Eggers, Stefanie; Sadedin, Simon; van den Bergen, Jocelyn; Robevska, Gorjana; Ohnesorg, Thomas; Hewitt, Jacqueline; Lambeth, Luke; Bouty, Aurore; Knarston, Ingrid; Tan, Tiong; Cameron, Fergus; Werther, George; et al.
Abstract Background Disorders of sex development (DSD) are congenital conditions in which chromosomal, gonadal, or phenotypic sex is atypical. Clinical management of DSD is often difficult and currently only 13% of patients receive an accurate clinical genetic diagnosis. To address this we have developed a massively parallel sequencing targeted DSD gene panel which allows us to sequence all 64 known diagnostic DSD genes and candidate genes simultaneously. Results We analyzed DNA from the largest reported international cohort of patients with DSD (278 patients with 46, XY DSD and 48 with 46, XX DSD). Our targeted gene panel compares favorably with other sequencing platforms. We found a total of 28 diagnostic genes that are implicated in DSD, highlighting the genetic spectrum of this disorder. Sequencing revealed 93 previously unreported DSD gene variants. Overall, we identified a likely genetic diagnosis in 43% of patients with 46, XY DSD. In patients with 46, XY disorders of androgen synthesis and action the genetic diagnosis rate reached 60%. Surprisingly, little difference in diagnostic rate was observed between singletons and trios. In many cases our findings are informative as to the likely cause of the DSD, which will facilitate clinical management. Conclusions Our massively parallel sequencing targeted DSD gene panel represents an economical means of improving the genetic diagnostic capability for patients affected by DSD. Implementation of this panel in a large cohort of patients has expanded our understanding of the underlying genetic etiology of DSD. The inclusion of research candidate genes also provides an invaluable resource for future identification of novel genes.